Investigation power: the ineffectiveness of police investigation in Malaysia / Muhammad Sabri Mohd Raziff - Mohd Raziff, Muhammad Sabri (2018)
This research concerned on the Criminal Procedure Code. The right of investigating officer to complete the investigation paper. Many investigation officer been keen accused wrongly because the investigation paper cannot be refered to the Deputy Public Prosecutor in stipulated time. Many complaint concern corruptions, not having integrity and being lazy. This accusation can make any of investigating officer’s morale to come down because of negative thoughts of certain people who do not know the procedure which has to followed by the investigating officer. This show failure of government to help investigating officer to complete the investigation paper. New amendment of the law is necessary and government must introduce the new law for the purpose enabling the investigating officer to complete investigation paper within stipulate a time without fail.